Răspuns :
y=-2-3x ⇔y=-2-3x ⇔y=-2-3x ⇔ y=-2-3x⇔y=-2+3⇔y=1
-5x-3(-2-3x)=2 -5+6+9x=2 4x=4 x=-1 x=-1 x=-1
-5x-3(-2-3x)=2 -5+6+9x=2 4x=4 x=-1 x=-1 x=-1
[tex] \left \{ {{3x+y=-2} \atop {-5x-3y=2}} \right. =\ \textgreater \ \left \{ {{y=-2-3x} \atop {-5x-3(-2-3x)=2}} \right. =\ \textgreater \ \left \{ {{y=-2-3x} \atop {-5x+6+9x=2}} \right. =\ \textgreater \ \left \{ {{y=-2-3x} \atop {4x=-4}} \right. =\ \textgreater \ \\ \left \{ {{y=-2-3*(-1)} \atop {x=-1}} \right. =\ \textgreater \ \left \{ {{y=1} \atop {x=-1}} \right. [/tex]
[tex]S={-1, 1}[/tex]
[tex]S={-1, 1}[/tex]